2007
DOI: 10.1007/s00403-007-0767-4
|View full text |Cite
|
Sign up to set email alerts
|

Administration of substance P during a primary immune response amplifies the secondary immune response via a long-lasting effect on CD8+ T lymphocytes

Abstract: Atopic dermatitis can be exacerbated or induced by scratching or psychological stress; both cause the release of substance P (SP) from sensory nerves. Therefore, SP may have an etiological role in mechanisms underlying AD. Here, we show that administration of SP during the primary immune response (PIR) imprinted long-lasting pro-inflammatory immunity, resulting in exacerbation of the secondary immune response (SIR) in the absence of further SP. Five days after sensitization with dinitrofluorobenzene (DNFB), ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Based on the current observation that up-regulated expression of SP in CD8 + T cells of AD, we believe that CD8 + T cells are more likely a causative cell type in the development of AD. A study that demonstrates a proinflammatory effect of SP on exacerbation of inflammation via long-term and indirect action on CD8 + T lymphocytes may support our hypothesis [32]. …”
Section: Discussionsupporting
confidence: 71%
“…Based on the current observation that up-regulated expression of SP in CD8 + T cells of AD, we believe that CD8 + T cells are more likely a causative cell type in the development of AD. A study that demonstrates a proinflammatory effect of SP on exacerbation of inflammation via long-term and indirect action on CD8 + T lymphocytes may support our hypothesis [32]. …”
Section: Discussionsupporting
confidence: 71%
“…They also showed that the other members of the tachykinin family, neurokinins A and B, had no effect on the differentiation of naive and memory T cells (Cunin et al, 2011). Finally, administration of substance P during the primary immune response amplifies the secondary immune response by activating CD8+ T lymphocytes (Ikeda et al, 2007). …”
Section: Immunobiology Of Substance Pmentioning
confidence: 99%
“…Recently, Zhang et al 70 found that SP and CD8 + T cells (cytotoxic T cells that secrete an array of pro‐inflammatory cytokines) are likely to have a role in the pathogenesis of atopic dermatitis through releasing SP. In line with this, Ikeda et al 71 showed that SP leads to exacerbation of inflammation via a long‐term and indirect effect on CD8 + T lymphocytes. Interestingly, intravenous injection of SP increased the levels of IL‐4, IL‐6, and IL‐10 in the lesion site of the spinal cord injury 72 .…”
Section: Inflammationmentioning
confidence: 72%